Comparison of the service and reception between winning and defeated high-level table tennis athletes - Nikolakakis, A.; Telopoulos, P.; Lanzoni, I. M.; Mavridis, G. (Journal of Human Sport & Exercise, 2023)
The aim of the present study was to compare service and reception in winning and defeated Table Tennis athletes. The sample of the survey consisted of 64 games (34 men and 30 women) of the A1 Table Tennis Greek national league, where a total of 5,065 points were analysed between 33 male athletes and 18 female athletes, who are among the best 32 of the official Hellenic Table Tennis Federation ranking. The variables analysed were: service grip, service execution length, reception technique, reception movement, the point conquest of the serving athlete and the point advantage in the first three hits. The non-parametric-square test(x2) showed that statistically significant differences were found between winning and defeated men, in the length of the service, with winners having a more effective service and more offensive reception. As for the female athletes, statistically significant differences were found in the grip and length of the service between winning and defeated women, while it was found that the winners have better service, perform defensive shots in the reception, and have an advantage in the first three hits. The above findings will help high-level athletes, coaches, physical trainers and performance analysts in understanding the importance of serving and receiving in high-level Table Tennis.